Gitelman's and Bartter's syndromes: from genetics to the molecular basis of hypertension and more - Verdiana Ravarotto; Giovanni Bertoldi; Lucia Federica Stefanelli; Federico Nalesso; Lorenzo A Calò (Karger Publishers, 2022)
Background: Gitelman's and Bartter's syndromes (GS/BS) are rare genetic tubulopathies characterized by electrolyte imbalance and activation of the renin angiotensin aldosterone system (RAAS). These syndromes have intriguing biochemical and hormonal abnormalities that leads them to be protected from hypertension, cardiovascular and renal remodeling. Summary: In this review we explore the biochemical/molecular mechanisms induced by the activation of the RAAS and its counterregulatory arm which is particularly activated in GS/BS patients, in the context of blood pressure regulation. In addition, we report our findings in the context of COVID-19 pandemic where we observed GS/BS subjects being protected from infection. Key Messages: The intracellular pathways induced by Ang II starting from induction of oxidative stress and vasoconstriction, are crucial for the progression toward cardiovascular-renal remodeling and might be useful targets in order to reduce/halt the progression of Ang II/oxidative stress-induced cardiovascular-renal morbidity in several diseases.